Iron coordination chemistry with tetra-, penta- and hexadentate bispidine-type ligands - Börzel, Heidi; Comba, Peter; Linti, Gerald W. (Inorganica chimica acta, 2002)
Described is the synthesis of tetra-, penta- and hexadentate bispidine ligands with two tertiary amine and two, three or four additional donors (pyridine, phenolate or alcoholate; bispidine=3,7-diazabicyclo[3.3.1]nonanone, coordinating substituents at positions 2,4; 2,4,7; 2,3,4; 2,3,4,7) and of their hexa-coordinate iron(II) complexes. Crystal structural analyses reveal that all complexes are six-coordinate, with one or two co-ligands, and all structures with the tetradentate bispidine ligand are asymmetrical with respect to the two tertiary amine donors, with short FeN1 and long FeN2 bonds (N1: position 3, N2: position 7). This is the same structural type as found for the Jahn-Teller labile copper(II) compounds, the manganese(II) and chromium(III) complexes but different from copper(I), zinc(II) and some cobalt(II) complexes with MN1≥MN2. Additional donors at N2 modify the structures, but do not lead to a change to the other structural type; additional donors at N1 lead to structures with MN1∼MN2. Solution studies (NMR, UV-Vis, electrochemistry, magnetism) indicate that the co-ligands may be substituted by solvent, with the donors trans to N2 being more labile than those trans to N1, but the over-all structural properties in solution are similar to those in the solid state. The complexes are stable towards oxidation, all except one have high spin electronic configuration. The oxidation potentials strongly depend on the two co-ligands.